Сучасний стан викладання української мови в школах Закарпаття з мовами національних меншин - Андрея Певсе; Andreya Pevse; Pősze Andrea („RIK-U” Kiadó, 2019)
Abstract. The present paper deals with the situation of learning the Ukrainian language by the Hungarian minority living in Transcarpathia. As Ukrainian language is the official state language in Ukraine, so it is natural, that the knowledge of this languge is compulsory for all the citizens, when it is taught properly and the appropriate conditions are created for mastering the Ukrainian languge. The paper deals with the lack of these conditions and also presents the results of a survey. The proper education planning would solve the problems of mastering the Ukrainian language in Transcarpathia and among the repesentatives of natonial minorities in Ukraine.

Резюме. У даній роботі розглядається ситуація вивчення української мови угорською меншиною, яка проживає на Закарпатті. Так як українська мова є державною в Україні, тому природно, що знання цієї мови є обов'язковим для всіх громадян. Маємо зазначити, що для цього має викладатися належним чином і мають бути відповідні умови для оволодіння українською мовою. У статті йдеться про відсутність цих умов, а також наводить результати опитування.
The current State of Ukrainian Language teaching in Schools with National Minorities’ languages in Transcarpathia
Keywords: Україна; Ukraine; Закарпаття; Transcarpathia; мова; language